Studi Penjaminan Mutu Berbasis Sekolah Inklusi : Studi Upaya Peningkatan Dan Pemerataan Mutu Pendidikan - Husein, Ragil Muhammad; Herdiani, Maida Maulia; Rahmania, Talia; Ayyasy, Dhestha Tsabita; Arfinanti, Nurul (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to explore the implementation of School Based Management (SBM) at MAN 2 Sleman in improving the quality of inclusive education. This research uses a descriptive qualitative approach with a case study method. Data were collected through observation, in-depth interviews and documentation with a teacher who serves as the head of the Disability Service Unit (ULD) as well as the Vice Principal for Public Relations. The results showed that MAN 2 Sleman successfully managed the seven main components of MBS, including curriculum and learning, students, educators and education personnel, financing, facilities and infrastructure, school and community relations, and school culture and environment. Supporting factors include curriculum flexibility, teacher readiness and an inclusive school culture. However, the main challenge lies in the limited financial support specifically for the inclusion programme. Nevertheless, MAN 2 Sleman is able to create a friendly, equitable and supportive learning environment for all students, both regular and special needs. The findings suggest that implementing MBS can effectively improve the quality of inclusive education.